Evidence for an age-dependent decline in axon regeneration in the adult mammalian central nervous system - Geoffroy, Cédric G. (Cell Rep, 2016)
How aging impacts axon regeneration after central nervous system (CNS) injury is not known. We assessed the impact of age on axon regeneration induced by Pten deletion in corticospinal and rubrospinal neurons, two neuronal populations with distinct innate regenerative abilities. As in young mice, Pten deletion in older mice remains effective in preventing axotomy-induced decline in neuron-intrinsic growth state, as assessed by mTOR activity, neuronal soma size and axonal growth proximal to a spinal cord injury. However, axonal regeneration distal to injury is greatly diminished, accompanied by increased expression of astroglial and inflammatory markers at the injury site. Thus, the mammalian CNS undergoes an age-dependent decline in axon regeneration, as revealed when neuron-intrinsic growth state is elevated. These results have important implications for developing strategies to promote axonal repair after CNS injuries or diseases, which increasingly affect middle-aged to aging populations.